Thinking About Quality and Its Links with Strategic Management - Thomas, Howard (Institutional Knowledge at Singapore Management University, 1996)
This article by Mark Pruett and Howard Thomas highlights the fact that there is a variety of perspectives on quality, but that each of those perspectives contributes to an integrative, systemic view of what it means to manage for quality. That systemic view raises certain key issues about the way we think of the strategic management process, issues which merit renewed scrutiny in the light of quality management.